HBR's 10 must reads on strategy. (Boston, Mass. : Harvard Business Review Press, 2011)
Is your company spending too much time on strategy development--with too little to show for it? If you read nothing else on strategy, read these 10 articles. We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help you catalyze your organization's strategy development and execution. HBR's 10 Must Reads on Strategy will inspire you to: Distinguish your company from rivals; Clarify what your company will and won't do; Craft a vision for an uncertain future; Create blue oceans of uncontested market space; Use the Balanced Scorecard to measure your strategy; Capture your strategy in a memorable phrase; Make priorities explicit; Allocate resources early; Clarify decision rights for faster decision making. --
What is strategy? / Michael E. Porter -- The five competitive forces that shape strategy / Michael E. Porter -- Building you company's vision / James C. Collins and Jerry I. Porras -- Reinventing you business model / Mark W. Johnson, Clayton M. Christensen, and Henning Kagermann -- Blue ocean strategy / W. Chan Kim and Renée Mauborgne -- The secrets to successful strategy execution / Gary L. Neilson, Karla L. Martin and Elizabeth Powers -- Using the balanced scorecard as a strategic management system / Robert S. Kaplan and David P. Norton -- Transforming corner-office strategy into frontline action / Orit Gadiesh and James L. Gilbert -- Turning great strategy into great performance / Michael C. Mankins and Richard Steele -- Who has the D?: How clear decision roles enhance organizational performance / Paul Rogers and Marcia Blenko.
Title from title screen.
Includes bibliographical references and index.
Print version record.
OCLC control number change
Keywords: Strategic planning; Planning Techniques; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Strategic planning; elektronické knihy; electronic books